Effect of sago and tapioca starches on the physicochemical properties of expanded rice products coloured with red beetroot (Beta vulgaris) powder - Abdul Alam, N. A.; Karim, Roselina; Syed Muhammad, Sharifah Kharidah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
The aim of this study was to determine the effect of two local starches, sago and tapioca starches, at 20 % level of substitution on the physical properties and betanin content of extruded rice coloured with 7.4 % red beetroot powder. The moisture of each feed was adjusted to 10 % and it was extruded at 80 ºC, 100 ºC, 120 ºC and 160 ºC for the first, second, third and fourth zones of the extruder barrel, respectively, with 120 rpm screw speed and 40 rpm feeder speed. 100 % rice flour coloured with 7.4 % red beetroot powder was also extruded as the control. The results showed that the expanded rice product with sago or tapioca had better expansion compared to 100 % rice, while the expansion ratio of extrudates incorporated with tapioca was higher than that with sago. No significant difference was found in the density of the extrudates. Extrudate substituted with sago had the highest water solubility index but the lowest water absorption index. The hardness and crispness values for the expanded rice product containing sago were 16.97 kg and 110.07 kg.sec, respectively, while that containing tapioca were 14.48 kg and 92.77 kg.sec, respectively. Meanwhile, the hardness and crispness values for 100 % rice extrudate were 18.37 kg and 126.55 kg.sec, respectively. No significant difference was found between the redness, a* values of the extrudates. However, retention of betanin in the expanded product was the highest when its rice content was substituted with tapioca (36.6 % retention), followed by that substituted with sago (34.1 %) and without substitution (27.8 %). As a conclusion, addition of tapioca starch or sago starch can help to improve the properties of naturally coloured expanded rice product.